Reconsidering research experiences as admission criteria for clinical psychology and clinical science PhD programs. - Cristello, Julie V.; Bowdring, Molly A.; Waddell, Jack T. (Training & Education in Professional Psychology, 2025)
The lack of diversity in the psychology workforce significantly impacts psychological science, patient care, and the profession more broadly. One way to enhance diversity within our workforce is through the recruitment of diverse trainees into clinical psychology and clinical science PhD programs. Although clinical psychology and clinical science programs have taken meaningful steps to foster a more holistic review of applications, the continued emphasis on prior research experience during the admissions process may be contributing to the ongoing lack of diversity within training programs and, consequently, within the psychology workforce. In the current article, we explore various barriers that often hinder underrepresented students and their ability to acquire research experiences, including the following: limited access to research opportunities, a lack of mentorship and guidance, and financial constraints that prevent students from engaging in unpaid volunteer work. Additionally, we offer considerations for faculty when reviewing applications, such as applicant characteristics or qualities to prioritize, revisions to personal statement prompts, and standardized guidelines for recommendation letters. We hope that the proposed considerations encourage further discussion within and across programs about the current recruitment processes to promote a more diverse and inclusive student body.